Modulation of the inflammatory response to chitosan through M2 macrophage polarization using pro-resolution mediators. (January 2015) - Vasconcelos, Daniela P.; Costa, Madalena; Amaral, Isabel F.; Barbosa, Mário A.; Águas, Artur P.; Barbosa, Judite N.
Abstract: Tissue engineering and regenerative medicine have created a demand for biomaterials with specific functions such as the ability to modify the host immune response. The objective of this study was to evaluate the effect of two different pro-resolution lipid mediators, lipoxin A4 (LxA4) and resolvin D1 (RvD1), in the modulation of the inflammatory response to biomaterials through M2 macrophage polarization. This was investigated in vivo using a mouse air-pouch model of inflammation. Our results demonstrated that both LxA4 and RvD1 are able to shift the macrophage response to implanted Ch scaffolds to an M2 reparative response. The injection of these pro-resolution mediators caused a decrease in inflammatory cells recruited to the implant site together with higher numbers of F4/80 + /CD206 + cells (M2 macrophages) and lower numbers of F4/80 + /CCR7 + cells (M1 macrophages); it also induced a general decrease in several pro-inflammatory cytokines; and caused a significant decrease in the thickness and area of the fibrous capsule formed around the implanted scaffolds. In conclusion, the use of either LxA4 or RvD1 allowed the in vivo control of macrophage phenotypic profile and thus may play a significant role in regenerative medicine applications, namely through modulation of the inflammatory response.